2019
DOI: 10.1017/s0007485319000622
|View full text |Cite
|
Sign up to set email alerts
|

Coexistence of three specialist predators of the hemlock woolly adelgid in the Pacific Northwest USA

Abstract: The hemlock woolly adelgid (Hemiptera: Adelgidae: Adelges tsugae Annand) is an invasive insect, introduced from Japan to eastern North America, where it causes decline and death of hemlock trees. There is a closely related lineage of A. tsugae native to western North America. To inform classical biological control of A. tsugae in the eastern USA, the density and phenology of three native western adelgid specialist predators, Leucopis argenticollis (Zetterstedt), Le. piniperda (Malloch) (Diptera: Chamaemyiidae)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…In the Pacific Northwest, Leucotaraxis spp. larvae were also found during the time when A. tsugae adults of both generations were producing eggs (Kohler et al 2008, 2016, Grubin et al 2011, Rose et al 2020), and when aestivating sistens were present (Grubin et al 2011). It is possible that Le.…”
Section: Discussionmentioning
confidence: 98%
“…In the Pacific Northwest, Leucotaraxis spp. larvae were also found during the time when A. tsugae adults of both generations were producing eggs (Kohler et al 2008, 2016, Grubin et al 2011, Rose et al 2020), and when aestivating sistens were present (Grubin et al 2011). It is possible that Le.…”
Section: Discussionmentioning
confidence: 98%
“…Data from eDNA surveys in conjunction with traditional sampling techniques can also be used to advance the ecological knowledge of target species. Previous studies have found a temporal overlap of these two Leucotaraxis species during the larval stage when aggregating observations from multiple locations (Dietschler et al, 2021; Rose et al, 2020), but that adult emergence is temporally asynchronous at the site level (Dietschler et al, 2021; Neidermeier et al, 2020). Our study only found both species in the same tree sample in two out of the 21 samples where Leucotaraxis were detected, with overlap occurring in only the May 13 and October 10, 2020, sampling periods.…”
Section: Discussionmentioning
confidence: 99%
“…During the time of western collections for this study, we could expect to find three larval instars or puparia (enclosed or intact) of Leucotaraxis flies, and larvae of La. nigrinus on western hemlock foliage (Dietschler et al, 2021;Grubin et al, 2011;Kohler et al, 2016;Rose et al, 2020;Zilahi-Balogh et al, 2003). For the enumeration of A. tsugae on eastern hemlock, approximately half of the sampled Measuring the foliage while collecting and dividing can increase the probability of eDNA contamination and was thus avoided.…”
Section: Visual Inspectionmentioning
confidence: 99%